Proton transfer from 1,4-pentadiene to superoxide radical anion: a qtaim analysis (2012)
We studied the bis-allylic proton transferreaction from 1,4-pentadiene to superoxideradical anion (O2·־). Minima andtransition state geometries, as well asthermochemical parameters were computedat the B3LYP/6-311+G(3df,2p)level of theory. The electronic wavefunctions of reactants, intermediates,and products were analyzed within theframework of the Quantum Theory ofAtoms in Molecules. The results showthe formation of strongly hydrogen bondedcomplexes between the 1,4-pentadien-3-yl anion and the hydroperoxylradical as the reaction products. Theseproduct complexes (PCs) are more stablethan the isolated reactants and muchmore stable than the isolated products.This reaction occurs via pre-reactivecomplexes which are more stable thanthe PCs and the transition states. This isin agreement with the fact that the netproton transfer reaction that leads to freeproducts is an endothermic and nonspontaneousprocess.